INDONESIAN ISLAMIC POETS' AMBIVALENCE UNDER THE DUTCH COLONIALISM IN THE 1930S - Dwi Susanto (Akademika : Jurnal Pemikiran Islam, 2022)
Islamic poets' poetical themes expressed their spiritual experience in Indonesian literature during the 1930s. These themes had opposed to the Islamic movement at the time, which was fighting against colonial ideology. The objectives of this study are to look at why poets advocated oppositional views in the face of colonial discourse, as well as the poets' position within the Dutch colonial system in the 1930s. Thematic notions of Indonesian literary poets in the 1930s, biographical histories of poets, and colonial discourses in Indonesia in the 1930s were among the data sources used in this study. The result revealed that the poets adopted a romantic aesthetic mimicking strategy to portray the idea of their spiritual experience. In most colonial literature, the mimicry between the colonizer and the colonized nation heightens the ambivalence of the Indonesian human personality. Because of ethical adjustments and unacceptable ideal categories, this ambiguous attitude develops. Syncretism emerges as a result of the clash of Western and Eastern civilizations. The author's aesthetic mimicry strategy has implications for the poet's ambivalence: on the one hand, the poet follows Balai Pustaka's aesthetic pattern with an understanding of individualism, while on the other hand, the poet ignites the concept of Islamic symbolic memory as part of the construction of Indonesian cultural identity, as in the Indonesian Cultural Polemics from 1930 to 1942.